Molecular biological change in oral cancer, summary of our researches. Issue 1 (February 2015) - Yamamoto, Nobuharu; Onda, Takeshi; Sugahara, Keisuke; Nomura, Takeshi; Shibahara, Takahiko
Summary: Molecular biological search and identification of cancer have a variety of clinical significance. Microarray, proteomics and metabolome analyses are powerful analytical methods for rapid screening of tumor markers. From the results, it was revealed that a number of genes are specifically expressed in oral cancers. From the results of CAN and LOH analyses of the entire genome, three candidate gene loci (D1S1189, D1S2151, D1S2595) were identified on 1q31.1 region. From the results obtained by using array CGH, amplification of the 11q13 regions was observed in 30% of the group with lymph node metastasis, and a numbers of genes were located in the 11q13 regions, in which increase of the copy number was observed in only the group with lymph node metastasis. From the results of proteomics analysis, three protein spots, in which expression increased in a common manner with a oral cancer cell line, as well as 27 spots, in which expression decreased in a common manner with a oral cancer cell line, were identified from these cataloged spots. Seven spots of proteins that are specifically expressed in the whole saliva of oral cancer patients before a surgery and not detected from the whole saliva after the surgery or the whole saliva of a healthy subject were selected. In the metabolome analysis, peaks of 250 of the major metabolic substances (136 cations, 114 anions) were detected.